The association between number of shoulder diagnoses and positive clinical tests with self-reported function and pain: A cross-sectional study of patients with hypermobile joints and shoulder complaints. (December 2022) - Kjærbæk, Frederik; Juul-Kristensen, Birgit; Skou, Søren T.; Søndergaard, Jens; Boyle, Eleanor; Søgaard, Karen; Liaghat, Behnam
Abstract: Background: Patients with hypermobility spectrum disorder (HSD) and shoulder complaints may suffer from symptoms related to shoulder instability, laxity, and hypermobility. It is currently unknown whether having a more complex clinical status with several diagnoses (i.e., anterior instability (AI), multidirectional instability (MDI), and/or symptomatic localised shoulder hypermobility (LSH), relates to higher functional impairments and pain. Objectives: To investigate the associations between either ≤1, 2, or 3 clinical shoulder diagnoses (AI, MDI, and LSH) or the number (0–10) of positive clinical shoulder tests with shoulder function using the western Ontario shoulder instability index (WOSI, 0–2100, 0 = best) and pain intensity using numerical pain rating scale (NPRS, 0–10, 10 = worse). Design: Exploratory cross-sectional study. Method: From a randomised controlled trial, baseline data from 100 participants with HSD and shoulder complaints for at least three months were included. Associations were investigated using linear regression models, adjusted for age, sex, body mass index, and hand dominance. Results: Compared with having ≤1 diagnosis, neither participants with two (WOSI 76.9, 95% CI -136.3, 290.0; NPRS 0.3, 95% CI -0.9, 1.5) nor three (WOSI 35.5, 95% CI -178.5, 249.6; NPRS 0.1, 95% CI -1.1, 1.3) clinical shoulder diagnoses had significantly worse shoulder function or pain. Likewise, the number of positive clinical shoulder tests was not associated with function (WOSI -20.8 95%CI (−55.3, 13.7)) or pain (NPRS -0.1 95%CI (−0.2, 0.1)). Conclusions: In participants with HSD and shoulder complaints, having more additional shoulder diagnoses or increased number of positive shoulder tests were not related to functional impairments or pain intensities. Highlights: Patients with joint hypermobility have several coexisting shoulder diagnoses. Having more shoulder diagnoses is not associated with worse pain or function. Having more positive shoulder tests is not associated with worse pain or function. The presence of mechanical shoulder symptoms did not affect these findings.